Determination of pre-harvest interval for dimethoate and quinalphos in selected vegetables (Asian-Australasian Journal of Bioscience and Biotechnology, 2020)
The study was undertaken to determine the pre-harvest interval (PHI) for dimethoate and quinalphos in cauliflower, eggplant and hyacinth bean depending on Maximum Residue Limit (MRL) set by European Union. Six supervised field trials were conducted and sprayed with the recommended dose (2 ml/L of water) of each pesticide. Samples were collected at 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 and 12 days after spray (DAS). The collected samples were analyzed using Gas Chromatography (GC) with Flame Thermionized Detector (FTD) for the determination of pesticide residue. The quantities of residue were above MRL up to 9 DAS for quinalphos in cauliflower, 7 DAS in hyacinth bean, 8 DAS in eggplant; 11 DAS for dimethoate in cauliflower, 10 DAS in hyacinth bean, and 9 DAS in eggplant. At 11 DAS, no residue was detected from any of the tested samples except dimethoate in cauliflower. The determined PHI for quinalphos was 10 DAS in cauliflower, 8 DAS in hyacinth bean and 9 DAS in eggplant. In case of dimethoate it was 12 DAS in cauliflower, 11 DAS in hyacinth bean and 10 DAS in eggplant.Asian Australas. J. Biosci. Biotechnol. 2020, 5 (1), 42-47